STRATEGI BERMAIN PERAN UNTUK MENINGKATKAN PEMAHAMAN LAMBANG BILANGAN DI KELAS 1 SD NEGERI CIPAKU 2 KOTA BOGOR: Pendekatan Pembelajaran Aktif di Sekolah Dasar - Leny Hidayanti; Hendro Prasetyono (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to describe the implementation of role-play learning activities through a “mini-market” simulation in the first grade of SD Negeri Cipaku 2, Bogor City, as a strategy to help students recognize number symbols from 1 to 20. Early grade students are in the concrete operational stage of cognitive development, where learning is more effective when associated with real-life contexts and hands-on experiences (Piaget, 1972). Role-play as a method provides opportunities for students to engage actively, collaborate, and learn meaningfully in a fun atmosphere. In this activity, students act as sellers and buyers: sellers offer goods with price tags ranging from 1 to 20, while buyers bring play money with denominations from 1 to 20. This setting allows students to practice identifying, matching, and using number symbols in transactions. The study found that this method not only improved students’ ability to recognize and understand numbers but also enhanced communication, social interaction, and confidence in classroom activities. In addition, the role-play approach aligns with Vygotsky’s (1978) sociocultural theory, which emphasizes learning through social interaction and scaffolding. The results also show that contextual learning through simulation increases student engagement and reduces anxiety in learning mathematics, particularly in number recognition. This research suggests that role-play in a “mini-market” setting is an effective and innovative alternative for introducing number symbols, making mathematics more concrete, interactive, and meaningful for young learners. Teachers are encouraged to adopt similar contextual learning strategies to strengthen foundational numeracy skills.